Handbook of sleep medicine - Avidan, Alon Y.; Zee, Phyllis C. , 1954- (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"The handbook offers practical and easily referenced algorithmic flow diagrams. It provides the flexibility of a quick, easily referenced guideline whereas the chapters provide specific diagnostic tools and detailed reviews of treatments"